RECORDKEEPING AND DOCUMENT MANAGEMENT IN UKRAINE: FROM PAPER TO ELECTRONIC PRACTICES (by the example of Cherkasy region, Ukraine, 1970s–2013) (in English) - OTAMAS, INNA (Knygotyra, 2015)
The Ukrainian Research Institute of Archival Affairs and Records Keeping Solomíanska St., 24. Kyiv, 03110, Ukraine E-mail: Otamas@mail.ruAfter the formation of the independent state, the Ukrainian people’s interest in their own history and events of the past has significantly increased.. The shaping of national identity and preservation of historical collective memory plays an increasingly important role in these processes. This is to some extent true of the Cherkasy region which is one of the richest in Ukraine. Scientific research of historians and archival material which reflect the development of the workflow management systems in the society of the region is sufficient proof of this. Special role in the study of the region history is given to the State Archives of Cherkasy region, the leading experts of which during 1970-2013 period made a significant contribution to the implementation of recordkeeping standards and normative document regulation acts such as the Laws of Ukraine “On Electronic Documents and Electronic Document Management” and “On Electronic Digital Signature”, dated May 22th, 2003, etc. As document management traditions are being produced during the centuries, investigation of electronic records management is practically possible from its initial formation stage. On the one hand, the main task of the electronic records keeping, as a relatively new phenomenon, is to adopt the best principles of traditional document management; on the other hand, it is no less important to develop new approaches to recordkeeping management, taking into account the use of electronic documents. Therefore it is important, in our opinion, to consider the main problems that accompany the practices of electronic document management as the investigated object, taking the example of Cherkasy region.
Keywords: records keeping; document; management activities; archive